Role of Dual Energy CT in the Characterisation of Lung Lesions - Raj, Nidhi; Shetty, Bharath; Shetty, Bharath; ., Manisha; Hegde, Prasad; K, Ganesh (International Journal of Innovative Research in Medical Science, 2018)
Aim: To study the clinical utility of Dual energy CT in differentiating benign and malignant lung lesions. Introduction: Dual energy CT is emerging as a problem solving tool with rapid data acquisition. The images are acquired at two energy levels, namely 80 and 140 kVp. Changing the photon energy levels allow us to manipulate the tissue attenuation. Methodology: The study included patients referred to Department of Radio diagnosis at our hospital for evaluation of lung lesions. These patients underwent a plain CT study of thorax, routine contrast enhanced CT and dual energy CT protocols on a dual source dual energy Siemens Somatom Definition CT scanner. Comparison was done using intraclass correlation coefficient between plain and virtual non contrast CT values and between degree of enhancement and iodine overlay values. Lesions were defined as benign or malignant based on histopathological or clinical correlation. The diagnostic accuracy of dual energy CT for differentiating benign and malignant lesions using a 20 HU cut off was calculated using statistical tools. Receiver operating Characteristic analysis was performed to obtain cut off value with appropriate sensitivity and specificity. Results: 41 patients were involved in our study. CT numbers on virtual non enhanced and plain CT images showed good agreement. Degree of enhancement from dynamic contrast enhanced CT and iodine overlay showed good agreement. Diagnostic accuracy for malignancy using CT numbers on iodine overlay images showed good significance with a sensitivity of 94.29%, specificity of 68.75%, positive predictive value of 86.84%, negative predictive value of 84.62%. The overall accuracy was calculated to be 86.27. Using ROC analysis, we have proposed a cut off of 22.250 with a sensitivity of 91.4% and specificity of 75%. We concluded that Dual energy CT of thorax can be convincingly used in evaluation of lung pathologies to differentiate benign and malignant lesions with significant accuracy.